2013
DOI: 10.1016/j.rmed.2013.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of inspiratory and expiratory reactance in interstitial lung disease

Abstract: Our results suggest that ΔX5 is a characteristic feature of IOS measurements in ILD patients, which is clearly different from those in asthma and COPD patients. This within-breath X5 change in ILD might be associated with its severity and physiological abnormality, although further studies are needed to investigate its cause.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
61
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 19 publications
10
61
1
1
Order By: Relevance
“…A previous study using IOS showed the association between the presence of ILD and ΔX5 in a multiple linear regression analysis, and a significant negative correlation between ΔX5 and VC or diffusing capacity (51). In our study using MostGraph, however, inspiratory Fres best correlated with the FVC, FEV1, diffusing capacity, and fibrosis score, but ΔX5 showed no correlation (52).…”
Section: Interstitial Lung Disease (Ild)contrasting
confidence: 71%
“…A previous study using IOS showed the association between the presence of ILD and ΔX5 in a multiple linear regression analysis, and a significant negative correlation between ΔX5 and VC or diffusing capacity (51). In our study using MostGraph, however, inspiratory Fres best correlated with the FVC, FEV1, diffusing capacity, and fibrosis score, but ΔX5 showed no correlation (52).…”
Section: Interstitial Lung Disease (Ild)contrasting
confidence: 71%
“…Previous reports have shown significant correlations between spirometric indices and FOT measurements in patients with asthma,12 COPD,13 and ILD 11,14. However, the correlation coefficients were relatively low, and each report included only a small number of patients.…”
Section: Introductionmentioning
confidence: 94%
“…Seventeen studies in healthy children (33-49) and eleven in healthy adults (30; 50-59) were identified and presented in Figure 2A and B (children) and Table 2 (adults). Due to limited data, IOS parameter values other than R5 and X5 were not available at this time.…”
Section: Population Based Reference Valuesmentioning
confidence: 99%
“…Table 2 includes mean ± standard deviation (SD) of R5 and X5 values obtained from healthy adults with diverse geographical and ethnic backgrounds. Some R5 and X5 values in Table 2 were estimated using a regression equation (30; 50, 59) at a given height and age. For adults, both R5 and X5 values were similar regardless of demographic or geographical differences.…”
Section: Population Based Reference Valuesmentioning
confidence: 99%